The Effect of Coretax Implementation on Tax Compliance with User Satisfaction as a Mediator - Sihotang, Grace; Purba, Heddry; Pangaribuan, Hisar (Economics and Digital Business Review, 2026)
This study investigates the impact of system quality and perceived cybersecurity on the tax compliance of individual employee taxpayers, with user satisfaction as a mediating variable. Using a quantitative approach and causal research design, data were collected through an online questionnaire from 110 individual taxpayers who filed their 2025 annual income tax returns via Coretax in 2026. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. Results show that both system quality and perceived cybersecurity positively impact user satisfaction. Furthermore, system quality, perceived cybersecurity, and user satisfaction significantly influence tax compliance. User satisfaction mediates the relationship between system quality and tax compliance but does not mediate the relationship between perceived cybersecurity and tax compliance. The findings highlight the need for improved system quality and enhanced data security in Coretax to boost taxpayer compliance.